Feasibility Study Of Establishing A BPRS In Banjarmasin City From Financial, Human Resources And Technology Aspects - Muhaimin, Muhaimin (Innovative: Journal Of Social Science Research, 2022)
This research aims to analyze the feasibility study of establishing a BPRS in the city of Banjarmasin from financial, human resource and technological aspects. The data used is primary and secondary data. Primary data is in the form of questionnaires and interviews distributed to business actors and individuals, while secondary data is data taken from the Financial Services Authority (OJK), Bank Indonesia, and the South Kalimantan Central Statistics Agency. The data analysis used is a mixed method by combining qualitative descriptive analysis and quantitative analysis. The results of the research show that from a financial aspect the regional financial capacity of the Banjarmasin City Government has the financial capacity to establish a BPRS with capital investment of IDR. 7,000,000,000. , if viewed from the HR, technical and technological aspects, the limited number of BPRS and sharia bankers who are reliable and master sharia banking operations and consistently implement sharia principles is a fundamental opportunity for the establishment of BPRS and its development in the future.